1988
DOI: 10.1115/1.3243503
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Butterfly Valves as a Flow Controller

Abstract: Butterfly valves have been used for shut-off and throttling-control application. It is found that the information available on loss coefficients of butterfly valves for good throttling control is limited at present. This report investigates the performance of two different configurations of butterfly valve: perforated blades and different diameter of solid blades that allow partial opening of the valve at closed position. The experimental results support the suitability of a butterfly valve for good flow contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…However, there are other studies that dealt with the control of flow using different types of valves (Davis and Sorenson, 1969;Streeter, 1961;Eom, 1988;Hutchison, 1976), flow around cylinders of various length-to-width ratios (Bearman and Trueman, 1972), and the mechanism of controlling vortex shedding from rectangular bluff bodies (Mills et al, 1995).…”
Section: Introductionmentioning
confidence: 97%
“…However, there are other studies that dealt with the control of flow using different types of valves (Davis and Sorenson, 1969;Streeter, 1961;Eom, 1988;Hutchison, 1976), flow around cylinders of various length-to-width ratios (Bearman and Trueman, 1972), and the mechanism of controlling vortex shedding from rectangular bluff bodies (Mills et al, 1995).…”
Section: Introductionmentioning
confidence: 97%
“…Lacor and Hirsch (1988) also investigated the butterfly valve flows with Euler code in the immediate vicinity of the valve disk. Eom (1988) treated with the butterfly valve as a controlling device for flows. But none of them investigated three-dimensional throttled flow patterns with different valve openings.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce or remove the high pressure loss when the valve is slightly open, several small holes on the valve plate can be applied. (Eom, 1988;. The streamline patterns are topologically described in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Especially, the most difficult work is to generate grid system inside a valve, since the external and internal flow field seems to be mixed in the view of grid generation and physics of flow. Until now, the most researches on the throttle valve have focused on the pressure loss due to the valve and the characteristics of flow control (Eom, 1988;Addy et al 1985;Dutton, 1989, 1991;Caille and Laumonier, 1998), however few papers are found which investigate the general flow field according to the valve opening angles. Thus, in this paper the flow field inside a throttle valve used for a SI engine is computed numerically for several opening angles of the valve plate.…”
Section: Introductionmentioning
confidence: 99%